SIMULASI NUMERIK KARAKTERISTIK PEMBAKARAN PADA TANGENTIALLY FIRED BOILER DENGAN VARIASI SUDUT YAW - Hosanova, Rindra (SPECTA Journal of Technology, 2019)
Coal is one of the energy sources that widely used for electricity, the age of coal reserves only remain 56 years, so it is necessary to make a study to reduce the consumption rate of coal with make an improvement on boiler efficiency which use tangentially fired boiler because it has good combustion. There are a problem in this type of boiler such as unbalance temperature and temperature deviation in superheaters and reheaters of the boiler. This research is made to study the effect of yaw angle modification to temperature in boiler. Method that used in this research is Computational Fluid Dynamic (CFD). Coal yaw angle modification in this research are +5º, 0º, -5º, -10º, dan -15º. Coal yaw angle modification have an effect to temperature distribution, wider yaw angle then larger the temperature deviation. The best coal yaw angle configuration is at -5º because it has the least temperature deviation on the upper furnace which minimize the risk of overheat on superheaters and reheaters.   Keywords: CFD, yaw angle, tangentially fired boiler